Adverse effects from clenbuterol and ractopamine on nematode Caenorhabditis elegans and the underlying mechanism. - Ziheng Zhuang (Public Library of Science (PLoS), 2014)
In the present study, we used Caenorhabditis elegans assay system to investigate in vivo toxicity from clentuberol and ractopamine and the possible underlying mechanism. Both acute and prolonged exposures to clentuberol or ractopamine decreased brood size and locomotion behavior, and induced intestinal autofluorescence and reactive oxygen species (ROS) production. Although acute exposure to the examined concentrations of clentuberol or ractopamine did not induce lethality, prolonged exposure to 10 µg/L of clentuberol and ractopamine reduced lifespan. At relatively high concentrations, ractopamine exhibited more severe toxicity than clentuberol on nematodes. Overexpression of sod-2 gene encoding a Mn-SOD to prevent induction of oxidative stress effectively inhibited toxicity from clentuberol or ractopamine. Besides oxidative stress, we found that clentuberol might reduce lifespan through influencing insulin/IGF signaling pathway; however, ractopamine might reduce lifespan through affecting both insulin/IGF signaling pathway and TOR signaling pathway. Ractopamine more severely decreased expression levels of daf-16, sgk-1, skn-1, and aak-2 genes than clentuberol, and increased expression levels of daf-2 and age-1 genes at the examined concentration. Therefore, the C. elegans assay system may be useful for assessing the possible toxicity from weight loss agents, and clentuberol and ractopamine may induce toxicity through different molecular mechanisms.